Electronic Services
DOI: 10.4018/9781615209675.ch028
|View full text |Cite
|
Sign up to set email alerts
|

Business Models for M-Services

Abstract: The mobile Internet will dramatically change the technical architecture and the business logic of the communications services. The new services and the new architecture are specified by new standardization bodies. Business modeling is a good planning method for capturing the commercial value of the technical development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The fracture toughness of the MDPE, PB, and PP grades shown in FYg. 4 is inferior to that of WE-Stage I1 failures appear after approximately lo00 h for both PP and PB and 10,000 h for MDPE. The actual data presented in FYg.…”
Section: Long-term Properties Of Hot-water Polyokjh Pipes-a Reviewmentioning
confidence: 70%
See 2 more Smart Citations
“…The fracture toughness of the MDPE, PB, and PP grades shown in FYg. 4 is inferior to that of WE-Stage I1 failures appear after approximately lo00 h for both PP and PB and 10,000 h for MDPE. The actual data presented in FYg.…”
Section: Long-term Properties Of Hot-water Polyokjh Pipes-a Reviewmentioning
confidence: 70%
“…The apparently brittle fracture surface is covered with a great number of ruptured fibrils visible only in a n electron microscope. This transition is essentially always associated with a pronounced increase in the slope of the log hoop stress-log failure time line (1)(2)(3)(4)(5)(6)(7). The transition from Stage I failure to brittle fracture occurs at the shortest time for the XLPE pipe with the lowest gel content and at progressively longer times for pipes of materials with higher gel content (Fig.…”
Section: Behavior Of Polyolefin Pipesmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased ventricular action potential (AP) duration and QT prolongation have also been observed in diabetic animal models (Nobe et al 1990). It is also notable that the incidence of bundle branch block (Okamoto et al 1997;Eriksson et al 1998;Jouven et al 1999a,b;El-Atat et al 2004;Jeong et al 2004;Suarez et al 2005), bradyarrhythmias and atrioventricular (AV) block (Fairfax & Leatham, 1975;Rubler et al 1975;Grimm et al 1990;Podlaha & Falk, 1992;Movahed et al 2005;Movahed, 2007) is significantly higher in DM patients than in the general population. Movahed et al (2005) reported a significantly greater incidence of AV block in diabetic patients compared with non-diabetics, and the association persisted when adjusting for both coronary artery disease and congestive heart failure.…”
mentioning
confidence: 99%
“…The calculated VS is higher than the experiments because the miscut at Si/SiGe interfaces, which are known to suppress VS, 8,16 are not included in these simulations. Recent experimental efforts 10,29 focus on the use of flat substrates without miscuts. Here we focus on "flat" quantum wells since the primary goal of this work is study the effects of SiGe alloy disorder.…”
mentioning
confidence: 99%